The Foundation of the Political Ideology of Mohammad Reza Hakimi - Abdullah Nazarzadeh Oghaz (‫سیاست متعالیه‏, 2021)
No special political, social, and governmental approach or deployment has ever been expressed since the beginning of the school of Tafkik (distinguishment) by its founders so Hakimi is recognized in charge of explaining the different aspects of this school of thought. In this regard, the purpose of the present study is to investigate the place of politics and government in the school of Tafkik as mentioned in the works of Hakimi. Therefore, the main research question of the study aims to determine the foundations of the political and governmental ideology of Mohammad Reza Hakimi and his approach to the Islamic Revolution in Iran. The method of study is descriptive analysis and it relies on the hypothesis that the intellectual transformations of Hakimi can be interpreted within a “justice-centered” approach to the Islamic state and the profound impact of “function” on “theory” in his ideas. The results of the study show that the transformation of the political ideology of Mohammad Reza Hakimi before and after the establishment of the Islamic Republic of Iran has been from the guardianship of the Islamic jurist to Hey’ate-Nawwab in occultation and the Islamic state based on the guardianship of the Islamic jurist to the state of Masanekh.